A prospective open-label trial of long-acting liquid methylphenidate for the treatment of attention deficit/hyperactivity disorder in intellectually capable adults with autism spectrum disorder. (20th April 2020) - Joshi, Gagan; DiSalvo, Maura; Wozniak, Janet; Ceranoglu, T. Atilla; Yule, Amy; Surman, Craig; Fried, Ronna; Galdo, Maribel; Hoskova, Barbora; Belser, Abigail; Biederman, Joseph
Abstract: Objectives: This treatment trial is aimed at assessing the short-term tolerability and efficacy of liquid-formulation extended-release methylphenidate (MPH-ER) for the treatment of attention deficit/hyperactivity disorder (ADHD) in adults with high-functioning autism spectrum disorder (HF-ASD). Methods: A 6-week open-label trial (ClinicalTrials.gov: NCT02096952) was conducted in 15 HF-ASD adults (mean age 24.9 ± 4.6; male, 12 (80%)) suffering from moderate-severe ADHD. MPH-ER was administered based on a flexible titration schedule. Efficacy was assessed on clinician- and self-rated measures. Tolerability was assessed by documenting treatment-emergent adverse events (AEs) and other safety measures. Results: Short-term MPH-ER treatment was associated with significant improvement in ADHD severity (Adult ADHD Investigator Symptom Report Scale (AISRS) mean change (MC), −22.8 ± 8.8, P  < 0.001; Adult ADHD Self-Report Scale (ASRS) MC, −8.2 ± 15.3, P  < 0.001). Twelve (80%) participants were deemed responders, based on ≥30% reduction in AISRS score and an ADHD Clinical Global Impression-Improvement score ≤2. MPH-ER was well-tolerated (treatment-limiting AEs, 1/15; severe AEs, 1/15) at mean dose of 48.7 ± 15 mg/day. AEs were transient and experienced by 13/15 (87%) participants at mild to moderate severity. Frequently reported AEs were as typically expected (headache (53%), insomnia (33%), anxiety (33%), decreased appetite (27%)). Conclusions: Our findings suggest that MPH-ER is effective and well-tolerated in the treatment of ADHD in HF-ASD adults.